Factors affecting students’ satisfaction towards bus services in university - Md Yusof, Zahayu; Misiran, Masnita; Lee, Pei Pei; Ho, Tian Tian (MAXWELL Science Publication, 2014)
This study describes a statistical study of students’ satisfaction towards bus services in university. The objective of this study is to explore factors that influence student satisfaction on bus services in Universiti Utara Malaysia (UUM).Primary data were collected by distributing direct questionnaire to four hundred students in UUM.A factor analysis yielded three factors which are attitude of bus driver, reliability of the buses and facilities of buses.